Autophagy in antiviral innate immunity. (7th November 2012) - Richetta, Clémence; Faure, Mathias
Summary Several autonomous arms of innate immunity help cells to combat viral infections. One of these is autophagy, a central cytosolic lysosomal‐dependent catabolic process constitutively competent to destroy infectious viruses as well as essential viral components that links virus detection to antiviral innate immune signals. Ongoing autophagy can be upregulated upon virus detection by pathogen receptors, including membrane bound and cytosolic pattern recognition receptors, and may further facilitate pattern recognition receptor‐dependent signalling. Autophagy or autophagy proteins also contribute to the synthesis of antiviral innate type I interferon cytokines as well as to antiviral interferon γ signalling. Additionally, autophagy may play a crucial role during viral infections in containing an excessive cellular response by regulating the intensity of the inflammatory response. As a consequence, viruses have evolved strategies to counteract antiviral innate immunity through manipulation of autophagy. This review highlights recent findings on the cross‐talk between autophagy and innate immunity during viral infections.